Respectable femininity and career agency: exploring paradoxical imperatives - Fernando, Weerahannadige Dulini Anuvinda; Cohen, Laurie (Wiley, 2013)
This paper places respectable femininity at the very centre of career enactment. In the accounts of 24 Sri Lankan women, notions of being a ‘respectable’ woman recurred as respondents described how important it was to adhere to the powerful behavioural norms for women in their organizations and society. However while such respectability was vital for women's career progression, it ultimately restricted their agency and conflicted with other requirements for advancement. Based on our empirical findings, we propose that being a respectable woman was experienced as paradox, where at times it was seen as impossible to be both a good woman and a successful careerist. We highlight the implications of our findings for women's careers in South Asia and more widely.